2014
DOI: 10.5194/acp-14-8055-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ambient measurements of biological aerosol particles near Killarney, Ireland: a comparison between real-time fluorescence and microscopy techniques

Abstract: Abstract. Primary biological aerosol particles (PBAPs) can contribute significantly to the coarse particle burden in many environments. PBAPs can thus influence climate and precipitation systems as cloud nuclei and can spread disease to humans, animals, and plants. Measurement data and techniques for PBAPs in natural environments at high time-and size resolution are, however, sparse, and so large uncertainties remain in the role that biological particles play in the Earth system. In this study two commercial r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 87 publications
10
103
3
Order By: Relevance
“…Ultimately, further analysis methods, including clustering techniques (e.g., Crawford et al, 2015Crawford et al, , 2016Ruske et al, 2017), will likely need to employed to further improve discrimination between ambient particles and to reduce the relative rate of misidentification. It should also be noted, however, that a number of ambient studies have compared results of UV-LIF instruments with complementary techniques for bioaerosol detection and have reported favorable comparisons (Healy et al, 2014;Gosselin et al, 2016;. So while uncertainties remain, increasing anecdotal evidence supports the careful use of UV-LIF technology for bioaerosol detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, further analysis methods, including clustering techniques (e.g., Crawford et al, 2015Crawford et al, , 2016Ruske et al, 2017), will likely need to employed to further improve discrimination between ambient particles and to reduce the relative rate of misidentification. It should also be noted, however, that a number of ambient studies have compared results of UV-LIF instruments with complementary techniques for bioaerosol detection and have reported favorable comparisons (Healy et al, 2014;Gosselin et al, 2016;. So while uncertainties remain, increasing anecdotal evidence supports the careful use of UV-LIF technology for bioaerosol detection.…”
Section: Discussionmentioning
confidence: 99%
“…Both the WIBS and UV-APS, in various version updates, have been applied to many types of studies regarding outdoor aerosol characterization. For example, they have been important instruments: in the study of ice nuclei Mason et al, 2015;Twohy et al, 2016), toward the understanding of outdoor fungal spore concentrations (Gosselin et al, 2016;Saari et al, 2015a;O'Connor et al, 2015b), to investigate the concentration and properties of bioaerosols from long-range transport (Hallar et al, 2011), in tropical aerosol Whitehead et al, 2010Whitehead et al, , 2016Huffman et al, 2012;Valsan et al, 2016), in urban aerosol Saari et al, 2015b;Yu et al, 2016), from composting centers (O'Connor et al, 2015b), at high altitude Gabey et al, 2013;Perring et al, 2015;Ziemba et al, 2016), and in many other environments (Healy et al, 2014;Li et al, 2016;O'Connor et al, 2015a). The same instrumentation has been utilized for a number of studies involving the built, or indoor, environment as well (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Virtually every ambient measurement study performed with the WIBS or UV-APS to date has shown a dominant FBAP mode peaking at 2-4 µm in size Gabey et al, 2010;Toprak and Schnaiter, 2013;Healy et al, 2014). For example, the FBAP size distributions measured at each of the four sampling locations discussed here is shown in Fig.…”
Section: Auto-fluorescence Measurementsmentioning
confidence: 99%
“…fungal spores, bacteria, and leaf fragments). Detected particles are categorized as fluorescent biological aerosol particles (FBAP), which may broadly be considered a lower limit for the abundance of PBAP Pöhlker et al, 2012;Healy et al, 2014). FBAP were measured at four different locations (Table 1) concurrently during three focus periods in summer 2010 and fall 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the practicality of long-term, continuous, real-time monitoring and discrimination of at least some of these properties for the more common types has already been demonstrated, e.g. at rural and semi-rural background sites in Germany, Ireland and Finland (Healy et al, 2014;Toprak and Schnaiter, 2013;Schumacher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%